Stearic-oleic acid nanocarriers for cream formulation / Woo Juin Onn - Woo, Juin Onn (2014)
Lipid nanoparticles are colloidal carrier systems that have extensively been investigated for controlled drug delivery, cosmetic and pharmaceutical applications. In this work, a series of stearic-oleic acid nanoparticles (SON) with different oleic acid compositions were successfully prepared by melt-emulsification combined with ultrasonication method. The SONs prepared have average particle size range from 200 nm to 250 nm depends on the oleic acid concentration in the mixture. TEM micrographs showed that high oleic acid compositions in SON induced the formation of elongated spherical particles. Encapsulation efficiency of SONs increased from 50% to 70% for both salicylic acid and lidocaine as increasing the oleic acid composition in the mixture. Differential scanning calorimetry analysis showed that the SONs prepared have lower crystallinity as compared to pure stearic acid. Different oleic acid composition in the mixture gave different degree of perturbation to the crystalline matrix of SONs hence result in lower degrees of crystallinity, thereby improve their encapsulation efficiencies. The optimized formulation, SON with 30 wt% was further incorporated into cream and evaluated the in vitro release for payload ingredients. The in vitro release showed a gradual release for 24 hours that strongly indicates the incorporation of payloads in solid matrix of SON and thus prolonged the release for both salicylic acid and lidocaine. Cream formulations with SONs containing salicylic acid and lidocaine showed about 3 times slower release rate as compared to their solution form, suggesting the potential use of SONs as carriers to improve therapeutic efficacy in cosmetic and pharmaceutical products.